Bio-oil derived hierarchical porous hard carbon from rubber wood sawdust via a template fabrication process as highly stable anode for sodium-ion batteries. (December 2019) - Muruganantham, Rasu; Hsieh, Tzu-Hsien; Lin, Chia-Her; Liu, Wei-Ren
Abstract: Novel rational design of hierarchical porous hard carbon as anode material for Na-ion storage is successfully prepared from rubber-wood sawdust via a ZnO-based hard template method. The as-synthesized hard carbon reveals a high specific surface area (820 m 2  g −1 ) with the hierarchical porous structure. In order to overcome poor initial coulombic efficiency in the first cycle, we use environmental-friendly water-based carboxymethyl cellulose with styrene butadiene rubber (CMC/SBR) binder instead of organic-based poly (vinylidene fluoride) (PVDF). The CMC/SBR binder delivers a reversible specific capacity of 275 mAh/g and maintains 192 mAh/g over 500 cycles at 100 mA/g. Moreover, PVDF binder exhibits a reversible capacity of 217 mAh/g and over the 500 cycles maintains 123 mAh/g. The Na-ion storage capacity contributes from the adsorption-intercalation mechanism of Na + ions into the prepared hard carbon for both electrodes. The contribution of surface capacitive for CMC-SBR sample is higher than that of PVDF binder, which demonstrates the enhanced capacity, high rate capability, and excellent cycle stability. This report confers a promising manner of a cost-effective method and eco-friendly abundant resource from bio-waste recycles to utilize the advanced sustainable clean green energy storage for future grid storage applications. Graphical abstract: Bio-oil derived hard carbon with hierarchical porous structure synthesized by a ZnO hard template fabrication process as a potential anode material for sodium-ion batteries with outstanding cycle life and high rate capability via an eco-friendly water-based binder. Image 1 Highlights: Biomass anode materials derived from rubber wood sawdustfor Na ion batteries are demonstrated. Hierarchical structure is demonstrated by hard template method. Two different binders of water soluble CMC/SBR and traditional PVDF binder are compared. The high-rate ultra-long term cycles around 5000cyclesat 15 A/gis approached.